2010
DOI: 10.1093/aje/kwq283
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Role of Social Disadvantage in Physical and Mental Health: Stressful Life Events, Health Behaviors, Race, and Depression

Abstract: Prevalence of depression is associated inversely with some indicators of socioeconomic position, and the stress of social disadvantage is hypothesized to mediate this relation. Relative to whites, blacks have a higher burden of most physical health conditions but, unexpectedly, a lower burden of depression. This study evaluated an etiologic model that integrates mental and physical health to account for this counterintuitive patterning. The Baltimore Epidemiologic Catchment Area Study (Maryland, 1993-2004) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
170
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 44 publications
12
170
5
Order By: Relevance
“…NSAL data indicate that binge eating disorder is the most common eating disorder among blacks in America [49]. This finding is consistent with the argument that African Americans may use food as a coping mechanism to deal with the high levels of environmental stressors they experience [45][46][47]. Furthermore, having a diagnosis of binge eating disorder has been associated with elevated risk of PD [50].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…NSAL data indicate that binge eating disorder is the most common eating disorder among blacks in America [49]. This finding is consistent with the argument that African Americans may use food as a coping mechanism to deal with the high levels of environmental stressors they experience [45][46][47]. Furthermore, having a diagnosis of binge eating disorder has been associated with elevated risk of PD [50].…”
Section: Discussionsupporting
confidence: 69%
“…An equally promising explanation for the lower levels of psychiatric disorders among African Americans has recently been put forth by Jackson and colleagues [45][46][47]. They argue that mental and physical health disorders are functionally related and that lower rates of psychiatric disorders in African Americans may come at the expense of higher rates of physical disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson and colleagues have argued that Blacks' low rates of depression despite of high rates of medical conditions compared to Whites may be due to their engagement in negative health behaviors (e.g., smoking or overeating) that may be associated with low psychological but high physiological damages [38][39][40][41]. Jackson's hypothesis suggests that the association between psychological and medical conditions among Blacks may not be as strong as Whites.…”
Section: Discussionmentioning
confidence: 99%
“…There may be differential response to stress behaviorally, as we know that some people respond to stress with loss of appetite and some respond with eating. Jackson and colleagues, for example, have suggested that Black individuals may use eating to cope with stress at a higher rate than White individuals [51,52]. In adults, those of higher initial BMI tend to gain weight under stress, whereas those who are lean tend to lose weight [53].…”
Section: Discussionmentioning
confidence: 99%